ANALISIS EFISIENSI FAKTOR PRODUKSI PADI SAWAH DALAM RANGKA KETAHANAN PANGAN DI DESA TUMPATAN KEC. BERINGIN KAB. DELI SERDANG - Sartika Frinces J Sitorus; Ramli Ramli (Departemen Ekonomi Pembangunan USU, 2013)
There is many factors internal and external factors that determine the level of rice production and rice production efficiency factor is very varied. This study aims to determine the efficiency of rice production factors. In the framework of food security in Tumpatan Village Deli Serdang regency.Case study method in the Village Tumpatan with multiple regression analysis techniques. Primary data were collected by interview by referring to kuissioner that has been prepared.Results showed partial seeds, fertilizers and pesticides have a significant and positive impact on rice production, labor is partially negative and significant effect on rice production. Variables simultaneously seed, fertilizer, labor and pesticides affect the rice production.Factors of production of seeds, fertilizers, and pesticides experiencing technical efficiency, and labor have not been efficient. Variables simultaneously seeds, fertilizer, pesticides and labor variables can explain the production of rice was 99.90% while the remaining 0.10% is explained byother variables that do not exist in the estimation model.Keywords: rice production, seed, fertilizer, labor, pesticides and efficiency.